2016
DOI: 10.1002/slct.201600316
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Pyridophenoxazinones, a Class of Antiproliferative Compounds

Abstract: Microwave (MW) irradiation allows to prepare a mini-library of pyridophenoxazinone derivatives, that are crucial intermediates in the synthesis of new antiproliferative compounds, active for human lymphoma/leukemia. The optimized procedure, consisting of a continuous input power of 50 W (808C) and a reaction time of 30 min, leads in very satisfactory yields to both regioisomers 5H-pyrido[2,3-a]phenoxazin-5-ones and isomeric\ud 5H-pyrido[3,2-a]phenoxazin-5-ones, starting from readily available quinoline-5,8-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nisco and co-workers prepared and examined various Pro-β 3 -amino ester catalysts for diastereo-and enantioselective aldol reactions under aqueous conditions. 277 The authors found that peptide 6.28, which possesses a β 3 -Trp-OMe residue with a free indole sidechain, gave the best results in the aldol reaction of 4-nitrobenzaldehyde and cyclohexanone, providing the product in >99% yield, 94:6 dr favoring anti, and 90% ee (Figure 100c). A π-π interaction might play a role in organizing the transition state.…”
Section: 4)mentioning
confidence: 99%
“…Nisco and co-workers prepared and examined various Pro-β 3 -amino ester catalysts for diastereo-and enantioselective aldol reactions under aqueous conditions. 277 The authors found that peptide 6.28, which possesses a β 3 -Trp-OMe residue with a free indole sidechain, gave the best results in the aldol reaction of 4-nitrobenzaldehyde and cyclohexanone, providing the product in >99% yield, 94:6 dr favoring anti, and 90% ee (Figure 100c). A π-π interaction might play a role in organizing the transition state.…”
Section: 4)mentioning
confidence: 99%
“…De Nisco et al [62] synthesized a series of pyridophenoxazinone isomers 75a-f and 75*a-f with antiproliferative activity, while using quinoline-5,8-dione and 2-aminophenols as starting materials. Under conventional TH, they only obtained trace of desired compounds 75a-f and 75*a-f, while the MW assisted reactions lead to the desired products in good yields.…”
Section: Six Membered Ring Azaheterocyclesmentioning
confidence: 99%